Long‐Life Aqueous Organic Redox Flow Batteries Enabled by Amidoxime‐Functionalized Ion‐Selective Polymer Membranes. Issue 38 (9th August 2022) - Ye, Chunchun; Tan, Rui; Wang, Anqi; Chen, Jie; Comesaña Gándara, Bibiana; Breakwell, Charlotte; Alvarez‐Fernandez, Alberto; Fan, Zhiyu; Weng, Jiaqi; Bezzu, C. Grazia; Guldin, Stefan; Brandon, Nigel P.; et al.
Abstract: Redox flow batteries (RFBs) based on aqueous organic electrolytes are a promising technology for safe and cost‐effective large‐scale electrical energy storage. Membrane separators are a key component in RFBs, allowing fast conduction of charge‐carrier ions but minimizing the cross‐over of redox‐active species. Here, we report the molecular engineering of amidoxime‐functionalized Polymers of Intrinsic Microporosity (AO‐PIMs) by tuning their polymer chain topology and pore architecture to optimize membrane ion transport functions. AO‐PIM membranes are integrated with three emerging aqueous organic flow battery chemistries, and the synergetic integration of ion‐selective membranes with molecular engineered organic molecules in neutral‐pH electrolytes leads to significantly enhanced cycling stability. Abstract : Highly ion‐selective robust membranes are developed from a series of amidoxime‐functionalized Polymers of Intrinsic Microporosity (AO‐PIMs), which enable long lifetime operation of aqueous redox flow batteries (RFBs) using low‐cost organic redox molecules at benign near‐neutral pH, offering cost‐effective electricity storage for grid‐scale renewable power sources.